Decision-making algorithm based on the results of systematic monitoring of forested landscapes in the subsoil use territories of the Urals - LEBEDEVA, Tat’yana Anatol’evna (NEWS of the Ural State Mining University, 2021)
Relevance of the study. Currently, information obtained during monitoring, including monitoring of forest lands, is of particular importance for making informed decisions on the development of natural potential. A feature of these works today is the lack of combination of data collection procedures, their processing with models of structural elements of forest lands, which requires a solution to the problem under consideration. The aim is to form, according to the results of system monitoring, a system of interconnected decision-making algorithms in the field of forest land use in industrial regions. The methodology for the formation of a system of interrelated decision-making algorithms in the field of forest land use in industrial regions is based on the use of mathematical models of natural objects of forest ecosystems, natural phenomena in them and forest-forming processes, on the procedures of a comprehensive assessment and optimization of forest land use in industrial regions in accordance with current provisions of the concept of environmentally sustainable development of territories. Results and their application. The algorithms for decision-making in the use of forest lands based on the results of system monitoring are considered: substantiation of strategic indicators of sustainable development of forest lands in industrial regions in the face of modern challenges and risks; comprehensive ecological and economic assessment of the natural resource potential of forest lands; determination of leeways of permissible use of forest lands in industrial regions in specific climatic and socio-economic conditions; coordination of individual interests of land users on forest lands with public preferences for the development of industrial regions; multi-criteria optimization of the use of forest lands in industrial regions. The main principles of forecasting the parameters of a comprehensive assessment of forest lands, the use of the indicator of consumption of net primary products of forest ecosystems, the sequence of greening the economy of the use of forest lands in industrial regions, justification of concessions to the extreme values of particular criteria in multi-criteria optimization are given. The proposed additional indicators of sustainable development of forest areas in the Middle Urals, the results of calculations on the change in the natural resource potential of forest lands in the subsoil use area are presented; the substantiation of the multicriteria optimization of the use of raw material resources of forest lands is given. Conclusions. The proposed decision-making algorithms in the field of systemic monitoring of forest lands are intellectual support for users in the analysis of information in the field of land relations. They provide a substantive dialogue that allows you to form the necessary information in a user-friendly form, adjust the data processing process and make decisions.